Balance of Payments Manual, Sixth Edition Compilation Guide - Valdivia-Velarde, Eduardo; Razin, Tamara (Washington, D.C. : International Monetary Fund, 2014)
The Balance of Payments and International Investment Position Manual 6: Compilation Guide is a companion document to the sixth edition of the Balance of Payments and International Investment Position Manual (BPM6). The purpose of the Guide is to show how the conceptual framework described in the BPM6 may be implemented in practice and to provide practical advice on source data and methodologies for compiling statistics on the balance of payments and the international investment position. The Guide is not intended to be a stand-alone manual, and readers should be familiar with the BPM6.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet